Objects machines, objects of death and memory: the kantorian poïein (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
In this article, I will examine the poetic relationships between actors and stage objects in specific scenes of the theatrical performance "Wielopole-Wielopole," directed by Polish director Tadeusz Kantor. To accomplish this, I will first provide a brief definition of the terms "poetics" and "stage objects". To synthesize the concept of poetics, I will refer to Pareyson (2001). Regarding the semiotic study of stage objects, I will draw on the works of Ubersfeld (2005), Pavis (2005), and Fischer-Lichte (1999). Lastly, I will analyze the placement of objects in the director's related praxis.
Keywords: physicality; conscious action; stage design; props; signs